A FUML-Based Distributed Execution Machine for Enacting Software Process Models - Ellner, Ralf; Al-Hilank, Samir; Drexler, Johannes; Jung, Martin; Kips, Detlef; Philippsen, Michael (Proceedings 7th European Conference on Modeling Foundations and Applications, 2011)
OMG's SPEM standard allows for a detailed modeling of software development processes and methods, but only a rather coarse description of their behavior. This gap can be filled by extending SPEM with a fine-grained behavior modeling concept based on UML activities and state machines. In order to gain full benefit from detailed software process models including behavior, an automated enactment of these software process models is required. In theory, the operational semantics of UML activities as defined by OMG's FUML (Semantics of a Foundational Subset for Executable UML Models) could be used to instantiate and sequentially simulate software process models on a single computer. However, FUML is insufficient to execute software process models to drive realistic projects with large and geographically spread teams. FUML lacks support for distributed execution in order to guide and support team members with their concurrent activities. FUML also does not fulfill key requirements of software processes, in particular requests for human interaction. Additionally, FUML requires explicit modeling of auxiliary user specific attributes and behavior of model elements, which is a cumbersome, repetitive and error-prone task and leads to non-reusable standard software process models. We present the required FUML extensions to support distributed execution, human interaction, and to weave in user specific extensions of the execution machine. With these FUML extensions it becomes feasible to enact reusable standard software process models in realistic projects. © 2011 Springer-Verlag.
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD2.afumlb

A New Approach to Consistency Control in Software Engineering - Heidenreich, Georg; Minas, Mark; Kips, Detlef (Proceedings of the 18th International Conference on Software Engineering (ICSE 1996), 1996)
Quality assurance methods as suggested by standards like ISO 9000 focus on the principle of review and feedback loops, which may be implemented by computer-based software process management including life cycle models, version control, and change tracking. Provided that the software process is modelled independently of concrete design methods, development tools, and software representations, a general representation of quality assurance methods can be obtained. In our paper we introduce such a high-level formalism, heavily exploiting some remarkable analogy between the software development process and distributed computations. Our approach is based on labelling each software element and product version during development. By using these labels one can coordinate versions, variant designs, and reconstruct elements of old versions automatically. Though our model is independent of particular design methods or programming formalisms, it can be parameterized with tools and compilers in order to be tailored to specific projects. Some applications are demonstrated for important problems of software project management that cannot be solved or even detected with nowadays standard methods, but that can easily be dealt with by using our new model
UnivIS-Import:2015-04-16:Pub.1996.tech.IMMD.IMMD2.anewap

An Integrated Tool Chain for Software Process Modeling and Execution - Ellner, Ralf; Al-Hilank, Samir; Jung, Martin; Kips, Detlef; Philippsen, Michael (Joint Proceedings of co-located Events at the 8th European Conference on Modeling Foundations and Applications (ECMFA 2012), 2012)
The Eclipse Process Framework (EPF) allows for a detailed modeling of software development processes and methods based on the Software and Systems Process Engineering Metamodel (SPEM) standard. A comprehensive electronic process guide may be generated from such a model. However, EPF and SPEM only support a rather coarse description of the behavior of software processes. As there is no support for automated enactment or simulation of these software process models, one cannot benefit from context-sensitive process guidance, automated process conformance checking, or automated progress tracking when enacting detailed software process models.   eSPEM (enactable SPEM) is an extension of the SPEM standard that supports UML activities and state machines for fine-grained behavior modeling. Its operational semantics is based on OMG’s fUML (Semantics of a Foundational Subset for Executable UML Models) and may be used to instantiate, simulate, and enact software process models. However, without a reasonable tooling for eSPEM the benefit for end users is still limited.   This paper presents an integrated tool chain based on eSPEM and Eclipse. The tool chain not only supports process modelers in modeling fine-grained eSPEM-based software processes, but also guides and supports project staff in working according to the process in a context-sensitive manner. It automates repetitive and cumbersome work like checking process conformance or progress tracking. Hence, it lets end users benefit from process modeling and enactment.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD2.aninte

Ein operationelles Modell zur Syntax- und Semantikspezifikation - Kips, Detlef (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1990)

eSPEM - A SPEM Extension for Enactable Behavior Modeling - Ellner, Ralf; Al-Hilank, Samir; Drexler, Johannes; Jung, Martin; Kips, Detlef; Philippsen, Michael (6th European Conference of Modelling Foundations and Applications, 2010)
OMG's SPEM - by means of its (semi-)formal notation - allows for a detailed description of development processes and methodologies, but can only be used for a rather coarse description of their behavior. Concepts for a more fine-grained behavior model are considered out of scope of the SPEM standard and have to be provided by other standards like BPDM/BPMN or UML. However, a coarse granularity of the behavior model often impedes a computer-aided enactment of a process model. Therefore, in this paper we present eSPEM, an extension of SPEM, that is based on the UML meta-model and focused on fine-grained behavior and life-cycle modeling and thereby supports automated enactment of development processes. © 2010 Springer-Verlag.
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.IMMD2.espema

Fallstudie zur Modellierung von Software-Entwicklungsprozessen auf Basis von SPEM 2.0 - Brunner, Maximilian; Jung, Martin; Kips, Detlef; Schmidt, Karsten (Software Engineering 2008: Fachtagung des GI-Fachbereichs Softwaretechnik, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.IMMD.IMMD2.fallst

Geplanter Inner Source: Ein Weg zu Profit-Center-übergreifenden Wiederverwendung - Riehle, Dirk; Kips, Detlef (2012)
Wiederverwendung von Softwarekomponenten verspricht, Softwareentwicklung schneller und günstiger zu machen und die Ergebnisqualität zu steigern. Trotz diverser methodischer Ansätze ist es für viele Softwareentwicklungsorganisationen schwierig geblieben, diese Ziele auch nur ansatzweise zu erreichen. Vor diesem Hintergrund bietet „Inner Source“, die Verwendung von Open-Source-Praktiken in der firmeninternen Softwareentwicklung, neue Chancen. Inner-Source-Software ist Software, die innerhalb eines Unternehmens über Profit-Center-Grenzen hinweg in Gemeinschaftsarbeit entwickelt wird und von allen Abteilungen genutzt werden kann. In diesem Artikel stellen wir die bisher gewonnenen Erfahrungen mit Inner-Source-Entwicklung dar, definieren organisatorische Gestaltungsmöglichkeiten und prognostizieren die Entstehung von Inner-Source-Organisationen, einer neuen Form der Organisation für die Wiederverwendung.
Keywords: Open source; inner source; software code reuse; knowledge sharing; firm-internal open source; open collaboration

Inner Source in Platform-Based Product Engineering - Riehle, Dirk; Capraro, Maximilian; Kips, Detlef; Horn, Lars (IEEE Transactions on Software Engineering, 2016)
Inner source is an approach to collaboration across intra-organizational boundaries for the creation of shared reusable assets. Prior project reports on inner source suggest improved code reuse and better knowledge sharing. Using a multiple-case case study research approach, we analyze the problems that three major software development organizations were facing in their product line engineering efforts. We find that a root cause, the separation of product units as profit centers from a platform organization as a cost center, leads to delayed deliveries, increased defect rates, and redundant software components. All three organizations assume that inner source can help solve these problems. The article analyzes the expectations that these companies were having towards inner source and the problems they were experiencing in its adoption. Finally, the article presents our conclusions on how these organizations should adapt their existing engineering efforts.
Keywords: Inner source; inner source foundation; product-line engineering; software platforms; engineering productivity

Using Multi Level-Modeling Techniques for Managing Mapping Information - Al-Hilank, Samir; Jung, Martin; Kips, Detlef; Husemann, Dirk; Philippsen, Michael (Proceedings of the 1st Int. Workshop on Multi-Level Modelling, ACM/IEEE 17th International Conference on Model Driven Engineering Languages and Systems, 2014)
Traditional modeling approaches support a limited set of instantiation levels (typically one for classes and another adjacent one for objects). Multi-level modeling approaches on the other hand have no such limit to the number of levels. As a consequence, an arbitrary number of levels may be used to define models, and the distinction between class and instance is redefined. The paper summarizes the experience gained from applying multi-level modeling techniques to a real application from the domain of development process improvement (DPI). The underlying case study has been conducted in cooperation with a large automotive supplier. We discuss the pros and cons of using multi-level modeling techniques and propose areas that we think would benefit from further research.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD2.usingm